Identification of essential β‐oxidation genes and corresponding metabolites for oestrogen degradation by actinobacteria - Hsiao, Tsun‐Hsien; Lee, Tzong‐Huei; Chuang, Meng‐Rong; Wang, Po‐Hsiang; Meng, Menghsiao; Horinouchi, Masae; Hayashi, Toshiaki; Chen, Yi‐Lung; Chiang, Yin‐Ru (Microbial biotechnology, 2022)
Summary Steroidal oestrogens (C18) are contaminants receiving increasing attention due to their endocrine‐disrupting activities at sub‐nanomolar concentrations. Although oestrogens can be eliminated through photodegradation, microbial function is critical for removing oestrogens from ecosystems devoid of sunlight exposure including activated sludge, soils and aquatic sediments. Actinobacteria were found to be key oestrogen degraders in manure‐contaminated soils and estuarine sediments. Previously, we used the actinobacterium Rhodococcus sp. strain B50 as a model microorganism to identify two oxygenase genes, aedA and aedB, involved in the activation and subsequent cleavage of the estrogenic A‐ring respectively. However, genes responsible for the downstream degradation of oestrogen A/B‐rings remained completely unknown. In this study, we employed tiered comparative transcriptomics, gene disruption experiments and mass spectrometry‐based metabolite profile analysis to identify oestrogen catabolic genes. We observed the up‐regulation of thiolase‐encoding aedF and aedK in the transcriptome of strain B50 grown with oestrone. Consistently, two downstream oestrogenic metabolites, 5‐oxo‐4‐norestrogenic acid (C17) and 2,3,4‐trinorestrogenic acid (C15), were accumulated in aedF‐ and aedK‐disrupted strain B50 cultures. Disruption of fadD3 [3aα‐H‐4α(3'‐propanoate)‐7aβ‐methylhexahydro‐1,5‐indanedione (HIP)‐coenzyme A‐ligase gene] in strain B50 resulted in apparent HIP accumulation in oestrone‐fed cultures, indicating the essential role of fadD3 in actinobacterial oestrogen degradation. In addition, we detected a unique meta‐cleavage product, 4,5‐seco‐estrogenic acid (C18), during actinobacterial oestrogen degradation. Differentiating the oestrogenic metabolite profile and degradation genes of actinobacteria and proteobacteria enables the cost‐effective and time‐saving identification of potential oestrogen degraders in various ecosystems through liquid chromatography–mass spectrometry analysis and polymerase chain reaction‐based functional assays. Actinobacteria were found to be key estrogen degraders in manure‐contaminated soils and estuarine sediments. In this study, we employed tiered comparative transcriptomics, gene disruption experiments, and mass spectrometry–based metabolite profile analysis to identify estrogen catabolic genes.